How designers destroyed the word - Gavrysh, O.; Kolesnikova, T. (ТОВ «Друкарня Мадрид», 2021)
The combination of good observation skills and good design principles is a powerful tool, one that everyone can use, even people who are not professional designers. Why? Because we are all designers in the sense that all of us deliberately design our lives, our rooms, and the way we do things. Good design often appears invisible – it doesn’t get in the way of the user. Now, what makes a design good or bad? And how to make design better than it is?
Keywords: designers; destroyed the word